Aspectos logísticos do escoamento do açúcar paulista: trecho usina-porto de Santos - Costa, Bruno Pompeu Corrêa da (2007)
Addressees the systematization of logistical and commercial aspects of São Paulo s sugar exports through Santos Port facilities. Local political and economical liberal transformations that took place by the beginning of 90 s had seen Estate assets being given to private investments (both in agricultural and port operations). As a result, this new institutional environment allowed the occurrence of hybrids corporate structures to coordinate logistical sugar and alcohol-ethanol exports from inland facilities to the Santos port. The main question is how this adaptation interferes on infrastructural and operational logistics management derived from new transactions within international sugar mayor traders. The main units of analysis are: i) São Paulo s state sugar producers (industrial plants) and port logistics providers; ii) port logistics providers and food trading companies. Results shall foster the comprehension on logistical process and relations amongst the three main actors across the sugar plantsport facilities chain. There are three goals to be achieved: i) identify the total extent of logistical domain across sugar s distributional channels via port of Santos; ii) how logistical assets and processes are developed or provided within those actors; iii) describe the difference among Santos port operations service providers, in relation value-added competitive basis. Theoretical framework blends logistics and supply chain management with foreign trade prospects as a guideline to collect data and empirical evidences. This works object is the São Paulo sugar plants-port of Santos facilities logistics chain.